Protein localization and interactions in the tomato ethylene signalling pathway - Zhong, Silin (2007)
Early studies of the tomato ethylene signalling network using yeast two-hybrid screen previously identified three novel proteins (IntCR22, 242 and 266) that could interact with a putative ethylene kinase LeCTR2 (Lin et al., 2003). In this study, it has been demonstrated that IntCR22 is a cytoplasmic UDP-glycosyltransferase and IntCR266 is a chloroplast metallo-proteinase homologue to the Arabidopsis FtSH5/VAR1, whereas IntCR242 encodes a novel chloroplast protein with a C-terminal histidine-rich domain. In order to gain more insight into the tomato ethylene signalling mechanism, the sub-cellular localization and protein-protein interactions of the tomato ethylene signalling components have been investigated by fluorescent protein labelling and yeast two-hybrid experiments. Three tomato ethylene receptors (ETR1, NR and ETR4) and a downstream regulator EIN2 have been found in the endoplasmic reticulum (ER). Three putative downstream MAPKK kinases (CTRs) could interact with the C-terminus of the ethylene receptor possibly on the cytoplasmic side of the ER, whereas a novel ethylene signalling component GREEN-RIPE was located in the Golgi. It was therefore concluded from the localization study that IntCR242 and IntCR266 were false positives from the yeast two-hybrid screen and could not interact in vivo with the ethylene signalling components. The results presented in this study, in line with previous ethylene research suggest a possible involvement of the plant endomembrane system in the ethylene signalling network. However, the question as to how the ethylene signal moves from the ER localized receptors to promote activation of genes for the transcription factors within the nucleus remains unsolved.